Biomassa para fins energéticos em área de regeneração natural de Ateleia glazioviana Baill - Fontoura, Mágda Rosa (2017)
This study aimed to evaluate the biomass for energy purposes in the natural regeneration area of Ateleia glazioviana Baill. For this, allometric models of volumetry were tested and determined to the energy properties of the different compartments of the trees: stem, branch and leaves, distributed in different diameter classes. The work was carried out in natural regeneration area in the municipality of Frederico Westphalen RS, Brazil; under geographic coordinates of 27 ° 23’08 “S and 53 ° 25’51” O, at 420 m altitude, with the installation of five plots of 4 X 25 m (100 m2) where the height and diameter of the chest height were measured at 1.30 m from the ground (DAP) of all individuals with 1.3 to 30.0 cm of DAP, totaling 163 trees,. Being selected 26 for the cut which were then distributed in 8 diameter classes: 1.8-3.7, 3.7-5.6, 5.6-7.5, 7.5-9.4; 9.4-11.3; 11.3-13.2; 13.2-15.1 e 15.1-17.0 cm. After the trees were felled, discs approximately 2.0 cm thick were removed at the following trunk positions: 0.10 m (base), 1.30 m (DAP), 25%, 50%, 75%, and 100% of Total height for the biomass assessments of the stem. While, for the determination of the biomass (BIO) of leaves and branches, stratified sampling was carried out along the canopy of the trees. The variables analyzed were higher calorific value (PCS), basic specific mass (ρb), energy productivity (PE), energy density (DE), fixed carbon content (CF), volatile material content (MV), ash content ( CZ). The results for biomass estimation, indicated that all model Spurr model and the one proposed by the authors, represented by the equation: MST = -5.6260 + 1.2986 * (dap²) * (h)) + εi presented the best performance with R 2a. of 0.846 and Sxy of ± 31.42%, being recommended for estimating biomass under the proposed conditions. In relation to the energetic properties, the diameter classes influenced the energetic properties of the wood, the highest values of PCS, BIO, PE and the smaller values of CZ were verified in the largest diameters. The components of the trees analyzed showed different yields and distributions for PCS, BIO, PE, CF, MV and CZ. The ρb and DE of the stem did not present increase or decrease variation with the increase of the diameter classes. The individuals of the eighth diameter class had the best conditions for the use of biomass for the production of energy in a natural regeneration area, thus recommending the use of trees with the largest diameters.